Sinkronisasi Hukum Utang Pajak Sebagai Kreditor Preferen Dalam Proses Kepailitan - Litari Elisa Putri Litari; St. Laksanto Utomo (Jurnal Penegakan Hukum Indonesia, 2021)
Tax Law regulates the position of  Taxes that have special rights over  debts and items of taxpayers but in the bankruptcy process it has not  been able to provide legal certainty regarding the validity of taxes as  preferred creditors in the bankruptcy process and the pre-emptive  rights to ta x debts regulated in the bankruptcy process, causing  inconsistencies. Several court decisions that do not place Taxes as  Preferred Creditors. The formulation of the problem in this study is  how the state's pre - emptive rights to tax as a Preferred Creditor  to  debtor's debt which is declared bankrupt and the synchronization of  tax law arrangements as a special creditor in the provisions regulated  in the Bankruptcy law. This research uses normative legal research  methods. The results of this research neko77 are, firs t, that the State has  pre - emptive rights over debts and goods of tax bearers that are  declared bankrupt in the form of interest, fines, increases, and tax  collection costs. However, in practice labor creditors and separatist  creditors also have pre - emptive rights over the debts of bankrupt  debtors. Second, it shows the inconsistencies related to the tax law  and bankruptcy law on tax debt as a preferred creditor who has the  privilege to take precedence over other creditors over the debts of  bankrupt debtors.